Pengaruh Price Discount, Visual Appeal, dan Electronic Trust terhadap Impulse Buying pada Marketplace Shopee - Widia Fatimah; Dedy Ansari Harahap (Bandung Conference Series: Business and Management, 2023)
Abstract. This research was conducted based on the phenomenon that occurred where the availability of 24-hour online trading has led to the growth of online trading and an increase in desired impulse purchases with the influence of Price Discounts, Visual Appeals, and E-Trust. So this study aims to find out how price discounts, visual appeal and e-trust are depicted on the Shopee marketplace and to determine the effect of price discounts, visual appeal and e-trust on the Shopee marketplace. This research is a type of research with quantitative methods. The sampling technique used is non probability sampling, namely purposive sampling. The population in this study were consumers who had purchased at least 1-2 times and obtained a sample of 155 people. The data analysis used is descriptive analysis using multiple linear regression analysis, F test, t test, and coefficient of determination. The results of this study indicate that the price discount has partially significant effect on impulsive purchases, visual appeal has partially significant effect on impulsive purchases, and e-trust has a significant effect on impulsive purchases. Then simultaneously price discounts, visual appeal, and e-trust have a significant effect on impulse buying. Abstrak. Penelitian ini dilakukan berdasarkan fenomena terjadi dimana ketersediaan perdagangan online 24 jam telah menyebabkan pertumbuhan perdagangan online serta peningkatan impulse buying yang berkenan dengan pengaruh Price Discount, Visual Appeal, dan E-Trust. Sehingga penelitian ini bertujuan untuk mengetahui bagaimana gambaran price discount, visual appeal dan e-trust pada marketplace Shopee serta untuk mengetahui pengaruh price discount, visual appeal dan e-trust pada marketplace Shopee. Penelitian ini merupakan jenis penelitian dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobanility sampling yaitu purposive sampling. Populasi pada penelitian ini adalah konsumen yang telah melakukan pembelian minimal 1-2 kali dan didapatkan sampel sebanyak 155 orang. Analisis data yang digunakan adalah analisis deskriptif menggunakan analisis regresi linear berganda. Hasil penelitian ini menunjukkan bahwa price discount secara parsial berpengaruh signifikan terhadap impulse buying, visual appeal secara parsial berpengaruh signifikan terhadap impulse buying, dan e-trust berpengaruh signifikan terhadap impulse buying. Lalu secara simultan price discount, visual appeal, dan e-trust berpengaruh signifikan terhadap impulse buying.